PENGARUH KEGIATAN MELUKIS PASIR TERHADAP KECERDASAN VISUAL SPASIAL ANAK USIA 5-6 TAHUN DI TK HANDAYANI KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Erna Ayu Lestari A.P; Daviq Chairilsyah; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: the purpose of this research is to know the effect of sand painting activity on spatial visual intelligence of child aged 5-6 years in TK Handayani Rambah Hilir Sub District Rokan Hulu Regency. This research is an experimental research using one group design with pre-test through observation sheet of spatial visual intelligence. The population in this study that children B classes totaling 15 children. The method used is pre-experiment with one group design that is experiment conducted on one group alone with no comparison group. The type of instrument used in this study was to use an observation guide to record the activities that occurred during the treatment given. Based on the result of hypothesis test, the effect of sand painting activity on spatial visual intelligence of children aged 5-6 years in TK Handayani Rambah Hilir Sub District Rokan Hulu Regency. This known t count of 23.189 with sig 0.000, because sig < 0.05 it can be concluded that there are differences in the intelligence visual spatial in significant students before and after using sand painting activities. Hypothesis test can be seen on t = 23.189> t table = 2.145. It has been suggested that there are significant differences in the results between the pretest and posttest. Sand painting activity to spatial visual intelligence of child aged 5-6 years in TK Handayani Rambah Hilir Sub District Rokan Hulu Regency to 63.1%Keywords: Sand Paiting , Spatial Visual Intelligence